2015
DOI: 10.15282/ijame.12.2015.13.0248
|View full text |Cite
|
Sign up to set email alerts
|

Performance and emission comparison of Karanja (pongamia pinnata), Pithraj (aphanamixis polystachya), Neem (azadira chtaindica) and Mahua (madhuca longofolia) seed oil as a potential feedstock for biodiesel production in Bangladesh

Abstract: Performance and emission comparison of Karanja (pongamia pinnata), Pithraj (aphanamixis polystachya), Neem (azadira chtaindica) and Mahua (madhuca longofolia) seed oil as a potential feedstock for biodiesel production in Bangladesh ABSTRACTThis paper investigates the production of biodiesel (BD) from karanja (Pongamia pinnata), pithraj (Aphanamixis polystachya), neem (Azadira chtaindica) and mahua (Madhuca longofolia) seed oil through acid esterification, followed by the investigation on the transesterificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Furthermore, higher CN of biodiesel fuel blends shorten ignition delay and thus the start of combustion advances. This results in a significantly longer residence time of higher temperature in the cylinder, creating more time for nitrogen to react with oxygen leading to higher NOx emissions [58]. It was observed that fuel blends number 1 and 18 showed the lowest and highest NOx emissions, respectively, which is in accordance with published literature [59].…”
Section: Nox Emissionssupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, higher CN of biodiesel fuel blends shorten ignition delay and thus the start of combustion advances. This results in a significantly longer residence time of higher temperature in the cylinder, creating more time for nitrogen to react with oxygen leading to higher NOx emissions [58]. It was observed that fuel blends number 1 and 18 showed the lowest and highest NOx emissions, respectively, which is in accordance with published literature [59].…”
Section: Nox Emissionssupporting
confidence: 88%
“…These features lead to an advance in start of fuel injection and a short ignition delay [23,24]. On the other hand, the major disadvantage of biodiesel is its higher viscosity [7,[25][26][27][28][29]. Higher biodiesel viscosity leads to pumping issues, poor atomization, poor cold-flow properties, coking of injectors, plugging of filters, increased carbon deposits on piston head, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of the fuels require modification according to the demands of the equipment. Several studies tried to use preheating in order to reduce the viscosity of the biodiesel [9,[23][24][25][26][27][28][29]. Some researchers showed that distillation process can be applied to improve the physical properties that affect atomisation characteristics of biodiesel for gas turbine application such as viscosity, density, and surface tension [30].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous experimental studies have already been conducted on the combustion and emissions of biodiesel fuel in conventional diesel engines [1][2][3][4][5]. Biodiesel is a liquid and transparent fuel, with an amber colour, entirely obtained from renewable sources such as vegetable oil (rapeseed, sunflower or other), produced by dedicated oil crops, from exhausted oils and food-borne animal/vegetable fats; the latter can be recovered through waste recycling, coming, for example, from the restaurant business, food processing industries and households [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%